Four weeks of finger grip training increases the rate of force development and the maximal force in elite and top world-ranking climbers - Levernier, G.; Laffaye, G. (The Journal of Strength and Conditioning Research, 2019)
The goal of this study was to assess the impact of a specific 4-week training program on finger grip in climbers; specifically, on the maximal force and the rate of force development (RFD) of finger muscles in isometric contraction. The participants were 14 French male rock climbers who took part in national and international bouldering competitions (at world-ranking and elite levels). They were divided into 2 samples. The experimental group performed a specific 4-week training program that included such exercises as suspensions on small holds at the rate of 2 times a week. The control group performed climbing exercises only. The maximal force and the RFD were recorded using a specific dynamometer in 3 different holding conditions (slope crimp, half crimp, and full crimp). Results reveal a significant gain of force for the slope crimp (+8%) and a high increase of the RFD in the first 200 ms of the force-time slope (between 27.5 and 32% for averaged conditions), suggesting a neural gain rather than a change in muscle-tendon structure. These results reveal that a 4-week training program is enough to improve the level of maximum force and the RFD in elite climbers. Bearing in mind that climbing will make its appearance in a future Olympic Games in the form of a combined competition, i.e., bouldering, speed climbing, and lead climbing, it will be crucial for each athlete to develop both a high level of force and RFD to be competitive.